(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In connection with the introduction of computer multimedia technologies in many areas of human life, including education, the concept, distinctive features, didactic potential of multimedia technology and multimedia visualization of educational information are revealed, which allows visual and accessible presentation of educational content; reveals the distinctive features of the new educational multimedia visibility and aspects of the implementation of the principle of visibility in teaching at a qualitatively new level. The problems and author’s approaches to the methodology of teaching future teachers to design and develop educational multimedia tools (primarily means of interactive multimedia visualization of educational information) are also considered; the main issues of the program of the special course "Multimedia teaching aids" (the program, which is one of the results of the research of the authors of the content of various courses in the study of educational multimedia).